The Reception of Seyyed Hossein Nasr’s Ideas within the Indonesian Intellectual Landscape - Widiyanto, Asfa (Studia Islamika, 2016)
This paper examines the appreciation and acceptance of Seyyed Hossein Nasr’s (b. 1933) ideas in the context of intellectual discourse in Indonesia. To do so, it investigates the translation of Nasr’s works into Indonesian, studies on Nasr’s thought, and quotations from Nasr’s works that emerge in the writings of some Indonesian intellectuals. It is especially the notions of Perennialism, “traditional Islam” and scientia sacra that throw light on the process by which his ideas have taken root and gained influence and acceptance in Indonesia. To be more specific, the article scrutinizes the impact of Nasr’s ideas and perspectives on the structure of thought of two Indonesian intellectuals, namely Nurcholish Madjid (1939-2005) and Komaruddin Hidayat (b. 1953). This paper also traces the roots of Nasr’s and Hidayat’s thought in the classical-medieval Islamic tradition, most specifically in Suhrawardi’s School of Illumination, and compares these with those of Madjid and Hidayat.DOI: 10.15408/sdi.v23i2.3002